Problem-sustaining patterns: redesigning the concept of mental disorder - Voerman, Sander A.; Strijbos, Derek W.; Staring, Anton B. P.; de Boer, Femke; van Dijk, Matthijs; Driessen, Jim; Glas, Gerrit; Goekoop, Rutger; Mulder, Annemarie; Tromp, Nynke; Verhaar, Marloes; van den Berg, David (Frontiers in Psychiatry, 2025)
We propose the concept of a problem-sustaining pattern as a revision of the established concept of mental disorder. The proposed concept preserves valuable features of the established concept, such as recognition of the client’s hardships and scientifically informed justification of specific interventions. However, several assumptions behind the established concept have been widely criticized, both in terms of their clinical and moral normativity as well as their ontological and empirical soundness. We argue that a focus on problem-sustainment allows us to reframe the issue of demarcation in a way that helps avoid stigmatization while clarifying the role of client agency in diagnosis. We also propose a shift toward thinking in terms of patterns of dynamic interaction, which is more in line with current developments in complexity science. We conclude the article with a discussion of further research that would be needed to address various questions raised by our proposal.